2018
DOI: 10.1002/cbic.201800310
|View full text |Cite
|
Sign up to set email alerts
|

Protonation of Nucleobases in Single‐ and Double‐Stranded DNA

Abstract: Single-stranded model oligodeoxyribonucleotides, each containing a single protonatable base-cytosine, adenine, guanine, or 5-methylcytosine-centrally located in a background of non-protonatable thymine residues, were acid-titrated in aqueous solution, with UV monitoring. The basicity of the central base was shown to depend on the type of the central base and its nearest neighbours and to rise with increasing oligonucleotide length and decreasing ionic strength of the solution. More complex model oligonucleotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 60 publications
4
21
1
Order By: Relevance
“…Therefore, one would expect that the most stable imine results from the most basic amine. Data presented in Table confirms this assumption, as the most basic cytosine has the most stable imine. This suggests that the main reason for cytosine being the primary target for isocyanates is due to its higher basicity, which facilitates its conversion to the reactive imine tautomer.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Therefore, one would expect that the most stable imine results from the most basic amine. Data presented in Table confirms this assumption, as the most basic cytosine has the most stable imine. This suggests that the main reason for cytosine being the primary target for isocyanates is due to its higher basicity, which facilitates its conversion to the reactive imine tautomer.…”
Section: Resultssupporting
confidence: 73%
“… a The p K a value refers to the first protonation state of guanine, which occurs in N7 . The relevant imine position is N1, so the corresponding p K a value is likely slightly lower. …”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, we optimized the geometry of the protonated oligonucleotide for two different positively charged systems being protonated on the A-N1 and on the G-N7 moiety, respectively (A-N1 and G-N7 are long known as the most likely protonation sites in isolated 2 0 -deoxyadenosine and 2 0 deoxyguanosine, respectively but also for nucleotides embedded in single stranded DNA. 1 ). All minimized structures were confirmed by Hessian calculations and no imaginary frequency were found.…”
Section: Theorymentioning
confidence: 99%
“…Under slightly acidic conditions, cytosine and adenine moieties become protonated and at even lower pH, also guanine is found protonated. 1 Nucleobase protonation has important structural implications. It is for instance often key to formation of non-canonical DNA structures such as i-motifs, four-stranded DNA structures that form in cytosine(C)-rich sequences and that are stabilized by stacks of protonated C -neutral C base pairs.…”
Section: Introductionmentioning
confidence: 99%
“…The p K values for nucleobase protonation in ribonucleoside 3′,5′-bis-ethylphosphates are ∼4.2 for C and ∼3.7 for A, and differ from those of deoxyribonucleoside 3′,5′-bis-ethylphosphates by only ∼0.1 p K units (65). Nucleobase protonation by gradual acidification of solutions of DNA followed the order C before A before G (94,95), and for 2–13 nt DNA, the p K values of both A and C increased with increasing number of residues (95). Further, experimental studies on a number of ribozymes and riboswitches have shown that the p K values of both A and C can shift toward neutrality (93).…”
Section: Resultsmentioning
confidence: 99%